Chart method for determining the liquid limit of soils - Prawat Ratanapisan; Dr. Chai Muktabhant; Prof. S.F. Michelin; Dr. Niwat Daranandana; Dean Milton E. Bender, Jr. (Bangkok : SEATO Graduate School of Engineering, 1965)
In the design and construction of highways and airfields, much time has been spent in determining the consistency limits, especially the liquid limit, by the standard AASHO Method. "The Chart Method" developed by the Washington State Highway Department is one of the rapid methods used to reduce the time required to perform liquid limit tests. A comparative study of the accuracy of this chart method was made by using local soil samples. It is concluded that it can be applied to soils in Thailand as a result of adjustment by the author using the method of least squares.
Thesis (M.Eng.) - SEATO Graduate School of Engineering
A thesis submitted in partial fulfillment if the requirements for the degree of Master of Engineering in the SEATO Graduate School of Engineering, Bangkok, Thailand.
Keywords: Soil moisture -- Mathematical models